اليات التحاسب الزكوي حول أنشطة التجارة الالكترونية البحتة - د. هشام عمر حمودي عبد (PROSPECTIVE RESEARCHES, 2023)
E-Commerce is one of the important results for modern technology. It is of two types: partial and pure. The pure one has a number of forms which allow its customers to get larger sums. In Islam, however, money must be of a halal source if it is to be used for Zakat. That's way business in Islam submits to a set of conditions to achieve halal money. Azzaka is the second must after assala in Islam. Accounting Azzaka has different mechanisms which differ according to the type of the sum, its amount and the purpose of its use. E-commerce activities will submit to zakat accounting mechanisms, but these mechanisms will vary depending on the activity. Some will submit to current money, some will submit to fixed money, and others will sumit to human wealth. In all, all submit to zakat accounting.